(untitled) (KASBIT Business Journal, 2018)
Ownership structure and dividend policy have been the debatable financial issue for the firms over the last few decades. This study aims to inspect the impact of ownership structure plus corporate dividend policy on the firm performance of oil and gas companies listed at KSE 100 Index in Pakistan. The Panel data was composed from the annual reports of oil and gas firms for 10 years from 2004 to 2014 on the annual basis. The Hausmen Test was implemented to examine the random or fixed affects, therefore the fixed affects were deployed to examine the impact of ownership structure as well as dividend policy on the firm performance. The results indicate that director`s ownership and institutional ownership does not have positive influence over the firm performance while individual shareholder`s ownership have positive influence over the firm performance. The results also indicate that ownership structure; Director Ownership, Institutional shareholder Ownership and Individual shareholders does not have positive influence over the corporate dividend policy.